1998
DOI: 10.1039/a802586j
|View full text |Cite
|
Sign up to set email alerts
|

New dinuclear platinum(I) complex obtained from thermal degradation of platinum(>0>)–triphenylphosphine complexes

Abstract: Thermolysis of [Pt(PPh 3 ) 2 (C 2 H 4 )], [Pt(PPh 3 ) 3 ] or of various complexes of the type [Pt(PPh 3 ) 2 (alkyne)] in toluene gave the dinuclear platinum() complex [(Ph 3 P)Pt{µ-C 6 H 4 (PPh 2 )-2}(µ-PPh 2 )Pt(PPh 3 )] in ca. 60% yield as a consequence of both C᎐H and P᎐Ph cleavage of co-ordinated triphenylphosphine. The complex, which has been identified by mass spectrometry, NMR ( 31 P, 195 Pt) spectroscopy and single-crystal X-ray diffraction analysis, is probably identical with some of the compounds fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…A comparison of our results with those obtained by Bennett et al 2 concerning the yields of the complexes [Pt 2 (m-o-C 6 H 4 PPh 2 )(m-PPh 2 )(PPh 3 ) 2 ] and 3 after different times of thermolysis of [Pt(C 2 H 4 )(PPh 3 ) 2 ] suggested that formation of this dinuclear complex results from in situ transformation of 3. However, heating an equimolar mixture of 3, [Pt(C 2 H 4 )(PPh 3 ) 2 ] and PPh 3 for 3 h did not afford any dinuclear complex (see Experimental section), although thermolysis of [Pt(C 2 H 4 )(PPh 3 ) 2 ] alone does, which confirms the importance of generating in situ the coordinatively unsaturated 14e fragment Pt(PPh 3 ) 2 .…”
Section: Methodssupporting
confidence: 83%
“…A comparison of our results with those obtained by Bennett et al 2 concerning the yields of the complexes [Pt 2 (m-o-C 6 H 4 PPh 2 )(m-PPh 2 )(PPh 3 ) 2 ] and 3 after different times of thermolysis of [Pt(C 2 H 4 )(PPh 3 ) 2 ] suggested that formation of this dinuclear complex results from in situ transformation of 3. However, heating an equimolar mixture of 3, [Pt(C 2 H 4 )(PPh 3 ) 2 ] and PPh 3 for 3 h did not afford any dinuclear complex (see Experimental section), although thermolysis of [Pt(C 2 H 4 )(PPh 3 ) 2 ] alone does, which confirms the importance of generating in situ the coordinatively unsaturated 14e fragment Pt(PPh 3 ) 2 .…”
Section: Methodssupporting
confidence: 83%
“…However, 1 shows a rare case of an unsymmetrical bridging l 3 -PR 2 ligand caused by an agostic-like interaction of a P-C sp2 bond with an unsaturated palladium centre. The isolation of complexes with bridging PR 3 ligands is relevant as reaction intermediates in the syntheses of l 2 -PR 2 phosphido derivatives from the corresponding l 2 -PR 3 tertiary phosphine complexes through the oxidative addition of the P-C bond to a metal centre [53][54][55][56][57][58], as well as to rationalize the intramolecular migration of the phosphine ligands. In the same context, the interaction between the P(2)-C(37) bond and the Pd(2) centre in 1 can provide a structural model as intermediates in phosphido transfer processes and even for the syntheses of l 3 -PR phosphinidene derivatives from the corresponding l 2 -PR 2 phosphido complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Examples are [Rh 2 (MeCO 2 H) 2 (μ-O 2 CMe) 2 (μ-2-C 6 H 4 PPh 2 ) 2 ], which is isolated from the reaction of dirhodium(II) tetraacetate with PPh 3 in glacial acetic acid, 2 and [Pt 2 (μ-PPh 2 )(μ-2-C 6 H 4 PPh 2 )(PPh 3 ) 2 ], which is one of the products of thermal decomposition of platinum(0)-triphenylphosphine complexes. 3,4 Interconversion between the two binding modes has also been demonstrated.…”
Section: ■ Introductionmentioning
confidence: 84%